Optimalisasi Peran Penyuluhan Urban Farming Teknik Vertikultur Pada Lahan di Perumahan Buana Green Subang Regency RT 60 RW 12 Kelurahan Soklat Subang - Ade Suryani; Abdul Robby Banny; Ajeung Nurlatifah; Albie Aditya Samudra; Asep Nurhidayat; Bayu Eka Supriatna; Dzikri Maulana; Ijang Samsu Rijal; Rohman Rohman; Wendy Leo Sanjaya; Tita Kartika Dewi (Jurnal Informasi Pengabdian Masyarakat, 2023)
Facts show that nowadays agricultural land tends to be narrower than residential land, both in urban and rural areas. This is what causes the lack of available land that can be used for farming activities, one of which is to produce vegetables or plants that are even easy to grow. One solution that can be done to overcome the urgency of the lack of land availability is urban farming. Urban Farming Verticulture technique is an agricultural and plantation activity carried out using only a small area of ​​land. And it is considered more effective and efficient. Therefore, ongoing educational activities are needed for the community about the benefits of urban farming using verticulture techniques through outreach methods and community assistance. The location of community service activities is carried out at Buana Green Housing, RT 60 RW 12, Soklat Village, Subang Regency. This service activity will take place from July 2023 to November 2023. We hope that by optimizing the urban farming extension and service methods, the housing community will be able to carry out minimalist farming and plantation activities to produce quality vegetables or plants, even though they only rely on a small amount of land in the area. residential yard or terrace. The results obtained from implementing this activity are increasing knowledge and implementation of velticultural cultivation in the Buana Green Housing community RT 60 RW 12 Soklat Subdistrict, Subang Regency.